Foot function assessment through kinematic and kinetic analysis - Mei, Q.; Gu, Y.; Ruan, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate toes` function while performing barefoot and shod running between habitually unshod and shod runners. Seven habitually male shod runners and six habitually male barefoot runners participated the running test. Kinematic and kinetic analysis were synchronously conducted. The habitually unshod runners showed significantly higher ankle eversion-to-inversion angle in the pushing-off phase than habitually shod runners. And forefoot loading reduced as the big toe of habitually unshod runners pushing ground under shod condition, with similar function of other toes among habitually shod runners. It is noted that the work of big toe and other toes lead to the decreased loading to the forefoot. This might be beneficial for the prevention of foot injuries, like plantar fasciitis and metatarsal fatigue fracture.